Pembelajaran Elektromagnetika Terapan Berbasis Augmented Reality: Kasus Sistem Koordinat - Rosyid Budiawan; Tri Nopiani Damayanti; Dwi Andi Nurmantris (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2017)
This paper aims to develop interactive media in the form of application of Applied Electromagnetics learning, based on Augmented Reality (AR) technology. This application is developed to visualize a point and vector in 3 dimensional coordinate system (3D) using marker and camera of Android smartphone/tablet. The system is able to visualize Cartesian coordinates, cylindrical coordinates, and spherical coordinates, points, and vectors into 3D form with optimal distance of 10–40 cm. Questionnaire results obtain MOS value of 4.31. This result suggests that learning integrated with AR technology can help improve understanding and stimulate students' motivation in exploring learning subject Applied Electromagnetics, especially the coordinate system.